الرمز في النثر الصوفي ـ مفهومه وإشكالاته - خليفة, خليفة; عبد اللاوي, يوسف (University of El-oued, 2021)
الملخص يتناول هذا المقال موضوع الرموز التي يستخدمها الصوفية في أدبهم وتخاطباتهم وتعبيراتهم عن المواجيد والأشواق والمكاشفات التي تعرض للصوفي في رحلة التعرف على الله، وقد استخدم الصوفية الترميز في الكلام خوفا من سوء فهم كلامهم، ودرءا لفتنة قد تصيب العوام ويكون ضررها أكثر من نفعها. ومن أهم هذه الرموز: رمز المرأة، ورمز الطير، ورمز الخمر، ورمز النور...الخ. Abstract The Sufi heritage has always been one of the richest products of Islamic thought, due to the depth of the Sufi experience itself, and this is what was manifested in a rich, varied and valuable heritage, and prose formed a tributary of this literature, and the features of depth and ardent emotion emanating from the nature of the mystical experience appeared. Prose that took the character of symbolism and sign, in order to hide the meanings and knowledge that was revealed to the people of Sufism on their way to God Almighty. It was imperative to pause at this rich and rich literature, and pause at these symbols and their meanings, and the methods of their connotations on the mystical meanings, especially as they deal with topics that touch the core of the Islamic faith.
مقال. Ex Professo. مج6. ع.1. جامعة الوادي
Keywords: الرمز؛ الصوفية؛ النثر؛ اإلشارة؛ الطريق; Keywords: Symbol; Sufism; Prose; Sign; Path.